THE ANALYSIS OF MARKETING MIX STRATEGY ANALYSIS TO IMPROVE POTENTIAL CONSUMERS (CASE STUDY ON AMANDA BROWNIES CUSTOMERS IN SALATIGA) - sundari, pipit; Tia Lestari, Wahyuni (UIN Salatiga, 2022)
This study aims to determine the effect of the Marketing Mix variable on increasing Potential Consumers (Case Study of Amanda Brownies, Salatiga ). The variables used in this study consist of independent variables, namely Product (X1), Price (X2), Place (X3), Promotion (X4), and Physical Evidence (X5) variables and the dependent variable is Potential Consumer (Y). The sample of this study is 96 respondents. Data collection techniques use questionnaire. The research findings the product has a significant positive effect on increasing potential consumers, price had a significant positive effect on increasing potential consumers, place has a significant positive effect on increasing potential consumers, promotion has a positive and significant effect on increasing sales volume and physical evidence has a positive and significant